Surgical management and clinical follow-up of post-coital severe vulvar hematoma in a 14-year-old adolescent girl: A case presentation: Adolescent girl and vulvar hematoma - Golbasi, Ceren; Golbasi, Hakan; Bayraktar, Burak; Ertas, İbrahim Egemen (Acta Biomedica Atenei Parmensis, 2021)
Background: Vulvar hematoma is often puerperal. A case of non-puerperal vulvovaginal hematoma is rare in the literature. There is no consensus on the management of vulvovaginal hematoma. In this study, we discussed the approach to a rare case of non-puerperal vulvar hematoma. Case: We present the case of a 14-year-old adolescent female with a severe vulvar non-obstetric hematoma that occurred after she had been illegally and voluntarily married. Conclusion: In conclusion; vulvar hematoma is the most common non-obstetric cause of perineal trauma and carries the risk of mortality by causing hypovolemic shock. The conservative approach is preferred for small and non-growing hematomas; however, surgical hematoma drainage is used for large and enlarging hematomas. Selective arterial embolization procedure is not common as the required equipment is not available in all healthcare facilities.